Errors when Determining Relative Number of Non-Hemolyzed Erythrocytes in Cryobiological Experiments - Zinchenko, V. D.; Buryak, I. A.; Volovelskaya, E. L. (Problems of Cryobiology and Cryomedicine, 2007)
Experimental requirements, during meeting of which the value of confidence interval for the integrity of cryopreserved erythrocytes of a donor makes 1.5–6.0% with 0.95 confidence probability, have been established.